2021
DOI: 10.1136/jitc-2021-003031
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine β-synthase mediated PRRX2/IL-6/STAT3 inactivation suppresses Tregs infiltration and induces apoptosis to inhibit HCC carcinogenesis

Abstract: BackgroundHepatocellular carcinoma (HCC) is characterized by inflammation and immunopathogenesis. Accumulating evidence has shown that the cystathionine β-synthase/hydrogen sulfide (CBS/H2S) axis is involved in the regulation of inflammation. However, roles of CBS in HCC development and immune evasion have not been systematically investigated, and their underlying mechanisms remain elusive. Here, we investigated the roles of CBS in tumor cells and tumor microenvironment of HCC.Methods236 HCC samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…PRRX2 was reported as an oncogene in several cancers, including hepatocellular carcinoma, prostate cancer, and colon cancer [ 21 , 22 , 42 ]. PRRX2 enhances invasion and migration in mammary epithelial cells and correlates with poor prognosis in breast cancer via activating TGF-β [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRRX2 was reported as an oncogene in several cancers, including hepatocellular carcinoma, prostate cancer, and colon cancer [ 21 , 22 , 42 ]. PRRX2 enhances invasion and migration in mammary epithelial cells and correlates with poor prognosis in breast cancer via activating TGF-β [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Tregs also regulate innate immune system cells (including dendritic cells, macrophages, neutrophils, γδ T cells, natural killer and innate lymphoid cells) [ 59 ]. The study also found that Tregs also played an important role in HCC [ 60 ]. Here ZSCAN20 was closely related to various subtypes of T cells, including memory T, effector T, Th1-like, effector Treg and exhausted T cell.…”
Section: Discussionmentioning
confidence: 99%
“…CCR4 is expressed in Tregs and Th17 cells [ 17 , 18 ]. Tregs are known to suppress antitumor immunity, thereby promoting carcinogenesis in certain settings [ 19 ]. Thus, CCR4+ Tregs may be involved in the development of GC after the eradication of H. pylori .…”
Section: Discussionmentioning
confidence: 99%